Novel quinoline-based fluorescent bioimaging probe, KSNP117, for sentinel lymph node mapping. Issue 24 (2nd June 2021) - Elbatrawy, Ahmed A.; Lee, Da Sol; Lee, Sang Bong; Jeon, Hui-Jeon; Lee, Sijoon; Kang, Kyung-ku; Sung, Soo-Eun; Han, Ye Ri; Cho, Sung Jin; Kim, Dong-Su; Kim, Kil Soo; Nam, Ghilsoo; et al.
Abstract : A novel near-infrared fluorescent imaging probe, KSNP117, was developed. Its excellent stability and biocompatibility were confirmed in vitro and in vivo, and its biomedical application for sentinel lymph node mapping was successfully demonstrated. Abstract : Fluorescent imaging agents with biocompatibility and high sensitivity are urgently required for the accurate detection of sentinel lymph nodes (SLNs). Herein, we report the design of a novel quinoline-based fluorescent probe, designated KSNP117, which can be applied as a biomedical imaging agent in the sensitive and quantitative detection of SLNs. KSNP117 exerted no adverse effects on the proliferation of ovary and immune cells and also showed excellent serum stability with photo-brightening effects. In vivo fluorescent imaging revealed the accumulation of KSNP117 in the SLNs of nude mice within 10 min post injection, without in vivo toxicity, which was consistent with the findings of ex vivo imaging. These results support the potential of KSNP117 as a promising lymphatic tracer for biomedical imaging applications.